Vascular Alterations in a Murine Model of Acute Graft-Versus-Host Disease Are Associated with Decreased Serum Levels of Adiponectin and an Increased Activity and Vascular Expression of Indoleamine 2, 3-Dioxygenase. Issue 11 (November 2016) - Schmid, Peter M.; Bouazzaoui, Abdellatif; Schmid, Karin; Birner, Christoph M.; Schach, Christian; Maier, Lars S.; Holler, Ernst; Endemann, Dierk H.
Graft-versus-host disease (GVHD) is the limiting complication after bone marrow transplantation (BMT), and its pathophysiology seems to be highly influenced by vascular factors. Our study aimed at elucidating possible mechanisms involved in vascular GVHD. For this purpose, we used a fully MHC-mismatched model of BALB/c mice conditioned according to two different intensity protocols with total body irradiation and transplantation of allogeneic (C57BL/6) or syngeneic bone marrow cells and splenocytes. Mesenteric resistance arteries were studied in a pressurized myograph. We also quantified the expression of indoleamine 2, 3-dioxygenase (IDO), endothelial (eNOS), and inducible NO synthase (iNOS), as well as several pro- and anti-inflammatory cytokines. We measured the serum levels of tryptophan (trp) and kynurenine (kyn), the kyn/trp ratio (KTR) as a marker of IDO activity, and adiponectin (APN). The myographic study showed a correlation of GVHD severity after allogeneic BMT with functional vessel alterations that started with increased vessel stress and ended in eccentric vessel remodeling, increased vessel strain, and endothelial dysfunction. These alterations were accompanied by increasing IDO activity and decreasing APN levels in the serum of allogeneic animals. The mRNA expression showed significantly elevated IDO, decreased eNOS, and elevation of most studied pro- and anti-inflammatory cytokines. Our study provides further data supporting the importance of vessel alterations in GVHD and is the first to show an association of vascular GVHD with hypoadiponectinemia and an increased activity and vascular expression of IDO. Whether there is also a causative involvement of these two factors in the development of GVHD needs to be further investigated.